ANALYZING SEVERAL FACTORS THAT INFLUENCE PEOPLE TO MAKE LOANS ONLINE - Marta Widian Sari; Andry Novrianto (UNIVERSITAS PAKUAN, 2020)
The purpose of this study was to determine the influence of cultural factors and psychological factors on people's decisions to apply for online loans (fintech) with religious factors as an intervening variable. The population in this study were the people of West Sumatra. The research sampling method was 100 people using quota sampling. Data processing with SmartPLS 3.0. The results of this study are Cultural Factors mediated by Religious Factors on Community Decisions to Apply for Online Loans (Fintech) and Psychological Factors mediated by Religious Factors on Community Decisions to Apply for Online Loans (Fintech).